Grape berry metabolism in field-grown grapevines exposed to different irrigation strategies - Souza, Cláudia R. de (2012)
The response of grape berry metabolism to vine water status was investigated in field grown grapevines (Vitis vinifera cv. Castelão) in southern Portugal. Water was supplied as: full irrigation (FI), to minimum water deficit corresponding to 100 % of crop evapotranspiration (Etc), partial rootzone drying (PRD) and deficit irrigation (DI), both corresponding to an irrigation amount of 50 % Etc, and a rainfed, i.e. no irrigation treatment (NI). In PRD, water was supplied to one side of the root system during each irrigation period, alternating sides every 15 d approximately. During the growing period, PRD and DI vines showed intermediate pre-dawn leaf water potential (Ψpd) values (around -0.4 MPa) by the end of the growing season, FI vines -0.2 MPa and NI -0.8 MPa. Berry weight as well as the content of glucose and fructose per berry increased in irrigated vines (PRD, DI, and FI) compared to NI vines. Although both malic and tartaric acid declined in non-irrigated vines, there was no significant difference between treatments at harvest. The activities of invertase, malate dehydrogenase and malic enzyme were not affected by irrigation throughout the ripening process. The contribution of other factors involved in the reduction of sugars and organic acids in berries of non-irrigated vines are discussed. These results show that deficit irrigation, like PRD and DI, do not have any negative impact on growth and quality of grape berries compared to fully irrigated vines, but may result in improved berry quality compared to rainfed vines.